Giant Cell Tumor within the Proximal Tibia after ACL Reconstruction - Takashi Takahashi; Lauren MacCormick; Jutta Ellermann; Denis Clohisy; Shelly Marette (Case Reports in Radiology)
26-year-old female with prior anterior cruciate ligament reconstruction developed an enlarging lytic bone lesion around the tibial screw with sequential imaging over the course of one year demonstrating progression of this finding, which was confirmed histologically to be a giant cell tumor of bone. The lesion originated around the postoperative bed, making the diagnosis challenging during the early course of the presentation. The case demonstrates giant cell tumor which originated in the metaphysis and subsequently grew to involve the epiphysis; therefore, early course of the disease not involving the epiphysis should not exclude this diagnosis.